Wealth Sharing for Conflict Prevention and Economic Growth : Botswana Case Study of Natural Resource Utilization for Peace and Development - Sebudubudu, David (World Bank, Washington, DC, 2014)
There are countries in Asia, Europe, the Middle East and even a few such countries in Africa that are using non-renewable resources to drive development and have not experienced conflict. South Africa, Namibia, Botswana, and Zambia are such typical cases in Africa. Instead, the presence of significant minerals in Botswana is associated with economic development and democracy as well as peace. This paper applies the "resource curse", thesis to the case of Botswana, a country that is rich in minerals, yet it has realized positive development thus avoiding conflict and 'the resource curse'. The focus of this study is to examine the experience of Botswana in using natural resources to promote equitable development and thereby avoid conflict which often results from selfish private or ethnic group interests that elsewhere have used natural resources to the exclusion of other groups in society. This study specifically looks at the conditions and factors that facilitated the absence of internal conflict in the extraction of natural resources in Botswana. The key questions answered are: what contextual conditions and factors facilitated the peaceful extraction of natural resources in Botswana?; and were these factors unique to Botswana or can they be replicated elsewhere?. The first chapter gives introduction. The second chapter deals with the socio-political setting of the chiefs' rule during the pre-colonial and colonial periods. The third chapter discusses Botswana's democracy and how it has evolved not only to democratize society but also to become a management culture of good governance for defining how the natural resources will be utilized for the country's development. Chapter four outlines the mineral resource base of Botswana and the policies and strategies used by government in ensuring that such resources were used for public good rather than the self-interest of either the leaders or mining houses. Chapter five focuses attention on cases of local conflicts relating to mineral and other natural resources around different parts of the country. Chapter six brings the issues together to explain Botswana's democratic and mineral dividends in attaining a high development success rate. Chapter seven presents conclusion.